2019
DOI: 10.1027/0269-8803/a000219
|View full text |Cite
|
Sign up to set email alerts
|

Interoception Enhanced via the Ears?

Abstract: Abstract. Heartbeat perception tasks are used to measure interoceptive accuracy. This paper explores the effect of reducing external auditory stimuli on heartbeat perception. Three samples (121 participants in total) performed a heartbeat perception task. Samples 1 and 2 wore ear-protectors and sample 3 did not. There were no differences in interoceptive accuracy between samples 1 and 2 but samples 1 and 2 showed significantly higher interoceptive accuracy than sample 3. These results suggest ear-protectors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Nevertheless, the current evidence suggests that the ear-protector manipulation transformed the HTT into a task that is inherently exteroceptive: HTT scores were significantly higher when ear-defenders were worn, and participants reported that the heartbeat pulse was more audible while wearing the eardefenders. Therefore, whilst scores on the HTT tend to improve as a result of the earprotectors, it should not be asserted that the manipulation increases IAcc (as suggested by Hall et al, 2019), given that IAcc purportedly measures sensitivity to internal bodily signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the current evidence suggests that the ear-protector manipulation transformed the HTT into a task that is inherently exteroceptive: HTT scores were significantly higher when ear-defenders were worn, and participants reported that the heartbeat pulse was more audible while wearing the eardefenders. Therefore, whilst scores on the HTT tend to improve as a result of the earprotectors, it should not be asserted that the manipulation increases IAcc (as suggested by Hall et al, 2019), given that IAcc purportedly measures sensitivity to internal bodily signals.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential manipulation of cardiac perception accuracy may involve reducing external auditory input. Indeed, in a recent quasi-experimental study, Hall, Lopes and Yu (2019) demonstrated that the use of noise-dampening ear-protectors resulted in significantly higher scores on the HTT (Schandry, 1981). However, due to the utilisation of a between-subjects study design and given the large variability in heartbeat detection scores (Murphy, Brewer, Hobson, Catmur, & Bird, 2018), it is not possible to ascertain from the work of Hall and colleagues (2019) whether IAcc can be manipulated within individuals by use of ear protectors.…”
mentioning
confidence: 99%
“…Therefore, whilst scores on the HTT tend to improve as a result of the ear-protectors, it cannot be asserted that the manipulation increases IAcc (as suggested by Hall et al, 2019),…”
Section: Discussionmentioning
confidence: 99%
“…Another potential manipulation of cardiac perception accuracy may involve reducing external auditory input. Indeed, in a recent quasi-experimental study, Hall, Lopes and Yu (2019) demonstrated that the use of noise-dampening ear-protectors resulted in significantly higher scores on the HTT (Schandry, 1981). However, due to the utilisation of a between-subjects study design and given the large variability in heartbeat detection scores (Murphy, Brewer, Hobson, Catmur, & Bird, 2018), it is not possible to ascertain from the Hall et al study whether IAcc can be manipulated within individuals by use of ear protectors.…”
mentioning
confidence: 99%